Effect of anesthetic technique on serum vascular endothelial growth factor C and prostaglandin E2 levels in women undergoing surgery for uterine leiomyomas. Issue 4 (April 2020) - Zhang, Yonghai; Yu, Jingfang; Yang, Fan; Zhao, Liyan; Ma, Ling; Zhang, Huiwen; Chen, Xuexin; Ma, Hanxiang
Objective: Angiogenesis is essential for growth and recurrence of uterine leiomyomas, and angiogenesis is mediated by vascular endothelial growth factor C (VEGF-C) and prostaglandin E2 (PGE2 ). This study investigated whether spinal anesthesia (SA) with continuous postoperative epidural analgesia attenuates postoperative changes in these angiogenic factors compared with general anesthesia (GA) with patient-controlled intravenous analgesia. Methods: Forty-four women with uterine leiomyomas undergoing abdominal myomectomy were randomized to receive either standard SA or GA. Blood samples were taken before anesthesia and at 48 hours after surgery for measuring serum VEGF-C and PGE2 levels, which were analyzed by using enzyme-linked immunosorbent assays. Visual analog scale pain scores were used to evaluate postoperative pain. Results: Serum VEGF-C and PGE2 levels were not significantly different preoperatively between the SA and GA groups, but they were decreased in each group at 48 hours after surgery compared with preoperatively. The change in pre- and postoperative VEGF-C levels was smaller in the GA group than in the SA group. Conclusions: Removal of uterine leiomyomas by surgery can reduce serum VEGF-C and PGE2 levels. The anesthetic technique affects serum VEGF-C levels, which are associated with angiogenesis in surgery for leiomyomas.